2018
DOI: 10.21534/ai.v19i2.118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Predigested Artificial Diet Using Papain Enzyme on the Degree of Protein Hydrolysis and Protease Enzyme Activity of Mud Crab (Scylla olivacea) Larvae at Zoea 2 and 3 Stages

Abstract: Haryati, Yushinta Fujaya, and Edison Saade. 2018. Effect of Predigested Artificial Diet Using Papain Enzyme on the Degree of Protein Hydrolysis and Protease Enzyme Activity of Mud Crab (Scylla olivacea) Larvae at Zoea 2 and 3 Stages. Aquacultura Indonesiana, 19 (2): 76-82. The ability of mud crab (Scylla olivacea) larvae to digest artificial diet depends on the availability of digestive enzyme. To enhance the larvaes capability to utilize artificial diet can be conducted by adding exogenous enzyme to the diet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…This has been proven by several previous studies such as that conducted by Hamzah et al (2015) showing that artificial diet predigest using papain enzyme at a dose of 4% is able to speed up the artificial feeding time for star pomfret (Tracinotus blochii) larvae to 12 days, where in Putri's research (2015) said that without giving predigest diet, artificial diet on star pomfret larvae could be given at the age of 18 days. Similar results were obtained from a study conducted by Haryati et al (2018) on the mangrove crab species (Scylla olivacea) showing that predigesting artificial diet for larvae using the enzyme papain 4.5% was able to speed up the artificial feeding time for mud crab larvae, namely at stadia zoea 2 , where in a previous study conducted by Haryati et al (2014) on mud crab larvae showed that protease, lipase and -amylase enzymes began to be produced at zoea 3 and at that stage it was suspected that new artificial diet could be given. Then further research by Haryati et al (2015) on mangrove crab (Scylla olivacea) larvae showed that protease, lipase and -amylase enzymes were given artificial diet to zoea 2 were still low.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This has been proven by several previous studies such as that conducted by Hamzah et al (2015) showing that artificial diet predigest using papain enzyme at a dose of 4% is able to speed up the artificial feeding time for star pomfret (Tracinotus blochii) larvae to 12 days, where in Putri's research (2015) said that without giving predigest diet, artificial diet on star pomfret larvae could be given at the age of 18 days. Similar results were obtained from a study conducted by Haryati et al (2018) on the mangrove crab species (Scylla olivacea) showing that predigesting artificial diet for larvae using the enzyme papain 4.5% was able to speed up the artificial feeding time for mud crab larvae, namely at stadia zoea 2 , where in a previous study conducted by Haryati et al (2014) on mud crab larvae showed that protease, lipase and -amylase enzymes began to be produced at zoea 3 and at that stage it was suspected that new artificial diet could be given. Then further research by Haryati et al (2015) on mangrove crab (Scylla olivacea) larvae showed that protease, lipase and -amylase enzymes were given artificial diet to zoea 2 were still low.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to the treatment using the papain enzyme, which had a higher enzyme activity, this was due to the activity of the protease enzyme in larvae aged 14, 17 and 20 days, diet that was predigested with the enzyme papain at a concentration of 4.5% which then played a role in triggering more optimal enzyme activity in hydrolyze diet protein. This is in line with the opinion of Haryati, et al (2018); Amalia, et al (2013); Hasan (2000) that the presence of enzymes in artificial diet can help and speed up the digestive process so that enough nutrients can be available for the growth and survival of fish. The more enzymes added to the diet, it will produce more protein which is hydrolyzed into amino acids, so it will increase the digestibility of the fish to the diet.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations